Design and Analysis of Compact Microstrip Circular Resonator with Slotted in Ground Plane as a Grain Moisture Sensor - Jain, Sweety; Thakare, Vandana Vikas (Review of Information Engineering and Applications, 2020)
The circular microstrip resonator (CMR) as a moisture sensor was analyzed for detecting the moisture content in grains. The design was proposed with the help of CST software at operating frequency 11.5GHz on X-Band. The size of the sensor was 13mm×13mm. The substrate was used FR4 with relative permittivity, thickness and loss tangent were 4.4, 1.676, and 0.001 respectively. The reflection coefficient was found -27.58dB at operating microwave frequency 11.5GHz, satisfied the condition (?-10dB). The voltage standing wave ratio (VSWR) was found 1.27 at selected frequency 11.5GHz, also satisfied the condition (VSWR? 2). The proposed design satisfied all the parameters and this design can be developed and determined actual moisture content (AMC), predicted moisture content (PMC) and mean relative error (MRE), when MRE will be find near to zero then sensor will be more accurate. Hence, it can be said that this sensor will be detect the moisture content (MC) in grains.